Collective bargaining and MNE (and their supply chains) - Ribeiro, Ana Teresa (2022)
The present article deals with the issue of collective bargaining vis-à-vis multinational companies and their supply chains. In fact, the national propensity of collective bargaining places this phenomenon at odds with the transnational character of those companies. And even though their supply chains foster economic growth and job creation, it is also true that, particularly in developing nations, they often fail to meet statutory requirements and to observe labour rights. We explore, therefore, the contribution that transnational collective bargaining could provide towards this issue (and the difficulties it faces), as well as other avenues, particularly consumer’s perception and pressure.